Multiple sclerosis - A review of recent advances in diagnostics and treatments - Wiśniewska, Klaudia; Ostańska, Agnieszka; Szafran, Adrianna; Terelak, Wiktor; Ciechański, Marcin; Witkowska, Edyta; Piasek, Laura; Godek, Grzegorz; Więcław, Kacper; Stańko, Katarzyna (Quality in Sport, 2023)
Introduction: Multiple sclerosis is a common chronic neuroinflammatory disease of the CNS with an autoimmune basis. It is the most common non-traumatic disorder that leads to disability in young adults. It occurs 3x more often in women. The quality of life of people suffering from multiple sclerosis is often significantly reduced. Objective: The purpose of this review is to analyze the latest information on the characteristics, diagnosis and treatment of patients with multiple sclerosis. Methods and matherials: A review of the literature available in the PubMed database published between 2016 and 2022, using the following keywords: "multiple sclerosis"; "pathogenesis"; "immunology"; "genetics"; “diagnostics” and "treatment." State of knowledge: Currently, there is no effective cure for multiple sclerosis but therapeutic options have increased over the past few years. Unfortunately, the effectiveness of disease-modifying therapies is too low and they cannot stop the progressive neurodegenerative process in the CNS. A recent development is the option of MS therapy using stem cells. This is to overcome the loss of nerve cells and increase the repair capacity of endogenous myelin. Conclusions: Although knowledge of the pathogenesis of the disease has advanced tremendously in recent years and many new therapeutic options have emerged, our knowledge is still incomplete. This poses a challenge for creating more drugs and halting the progression of the disease.